Characterization of Desert Truffles in the Great Moroccan Sahara: A Review - Imane Zniber; Hassan Boukcim; Lahsen Khabar; Marc Ducousso; Fatima Henkrar; Ayoub El Mouttaqi; Abdelaziz Hirich (Environmental Sciences Proceedings, 2022)
Desert truffles are edible mushrooms compulsorily living in symbiosis with plants’ roots. They are rich in essential nutrients and secondary metabolites, conferring therapeutic properties. In Morocco, around ten species can be found in semiarid and arid climate regions with low annual rainfalls and high average temperatures. They can be associated with the Cistus and Pinus species and some other species, but they are detected more often under the Helianthemum species. In this study, we present a short review of the distribution of Moroccan desert truffles in the Great Sahara, along with the progress achieved in their morphological and molecular identification and the evaluation of their nutritional content.